Do prognosis and clinicopathological features differ in young early-stage breast cancer? - Arikan, Akif Enes; Kara, Halil; Dülgeroğlu, Onur; Erdoğan, Esin Nur; Capkinoglu, Emir; Uras, Cihan (Frontiers in Surgery, 2022)
Background Breast cancer is the most frequently detected cancer and the leading cause of cancer-related death in women. Although it is mostly seen in older patients, breast cancer affects women aged 24 to >70 years, with poorer prognosis in young patients. Young age remains a controversial topic in the literature. This study aimed to identify subtype differences and the effect of age on early-stage breast cancer outcomes. Methods A total of 300 consecutive patients underwent surgery between 2011 and 2015 for early-stage breast cancer. Of these, 248 were eligible for this study and were divided into three groups: group Y (aged ≤35 years), group M (aged >35 and ≤45 years), and group E (aged >45 years). The clinical and pathological features and data related to recurrence, metastasis, and death were recorded. Results No statistical differences were found between groups regarding histopathological features except for higher histological grade and Ki-67 levels in group M. Additionally, group Y recorded no progression (recurrence or metastasis) or death. Disease-free survival was 117.8 months (95% CI 111.8–123.8) for group M, which was significantly shorter than that for group E (p < 0.001). Additionally, the hazard ratio (HR) for progression from group M to group E was 10.21 with significant difference (p = 0.003, 95% CI 2.26–46.08). However, the HR of group Y to group E was 0.04, without significance (p = 0.788, 95% CI 0.18–345 × 106). The overall 5-year survival was 100% in group Y, 98.8% in group M, and 99.3% in group E, without significance. Conclusion A very young age cannot be considered an independent risk factor for poor prognosis. Rather than age, histological grade and Ki-67 index are more important factors in early-stage breast cancer.